Hypertriglyceridemia — current status of the problem. Part II: primary and secondary hypertriglyceridemias, treatment options - A. A. Semenkin; A. N. Meshkov; M. V. Yezhov (Российский кардиологический журнал)
Hypertriglyceridemias are a heterogeneous group of pathologies differing in the mechanisms of triglyceride-rich lipoprotein increase, the composition of lipoproteins and related risks. This review article presents information on the profile and pathogenesis of various primary and secondary hypertriglyceridemias, as well as describes current potential of genetic diagnostics, drug and non-drug correction.